FACTORS THAT AFFECT TRANSPORT MODE PREFERENCE FOR GRADUATE STUDENTS IN THE NATIONAL UNIVERSITY OF MALAYSIA BY LOGIT METHOD - ALI AHMED MOHAMMED; ALAA A. SHAKIR (Journal of Engineering Science and Technology, 2013)
A study was carried out to examine the perceptions and preferences of students on choosing the type of transportation for their travels in university campus. This study focused on providing personal transport users road transport alternatives as a countermeasure aimed at shifting car users to other modes of transportation. Overall 456 questionnaires were conducted to develop a choice of transportation mode preferences. Consequently, Logit model and SPSS were used to identify the factors that affect the determination of the choice of transportation mode. Results indicated that by reducing travel time by 70% the amount of private cars users will be reduced by 84%, while reduction the travel cost was found to be highly improving the public modes of utilization. This study revealed positive aspects is needed to shift travellers from private modes to public. The positive aspect contributes to travel time and travel cost reduction, hence improving the services, whereby contributing to sustainability.